Sistem Identifikasi Minat dan Bakat Berbasis Multiple Intelligence dan Simple Additive Weighting - Imami, Marta Fairus Hani; Lutfi Hakim; Sepyan Purnama Kristanto; Yuniarta Syarifatul Umami (ZETROEM, 2024)
Interests and talents identification in children is generally carried out by psychologists who provide test services. But the procedures used are still manual and take a long time to get the results. In addition, the presence of psychologists is still limited and uneven in all regions of Indonesia. Therefore, in this study, a system was developed to identify children's interests and talents based on multiple intelligences which was developed by Howard Gardner with the Simple Additive Weighting method. This method is used to calculate the most dominant type of intelligence possessed by children based on a test device developed by psychologists using a Likert scale in the assessment of each question. Based on the results of testing carried out using black-box testing, it was found that all the features developed were 100% valid based on all the scenarios tested. In addition, the test results between the calculations in the application and manual with excel obtained a score of 100% valid which means that there is no significant difference between the two calculations. The output obtained from this system after the child has consulted is that the most dominant type of intelligence is obtained along with an explanation related to that intelligence, how to handle it, recommended extra-curricular activities and articles related to the type of intelligence. This application was developed with two actors, namely admin and child which was developed with the Laravel framework.